The management and leadership of educational marketing research, practice and applications - Oplatka, Izhar; Hemsley-Brown, Jane, 1950- (Bingley, U.K. : Emerald, 2012)
The introduction of educational markets into public and higher education in many countries has led to more competitive environments for schools and higher education institutions. This, in turn, has led to an increased priority being given by school leaders to the marketing of their institutions, largely because the survival of many educational institutions is now dependent on their capacity to maintain or increase their 'market share' of students, funding and resources. This book presents the works of leading scholars and researchers in the field of educational marketing who handle issues of student retention; trust; building relationships with parents, curriculum marketing, strategic marketing, and market orientation in the educational arena. Special attention is given by the authors to the promotion of education in respect to school innovation, success, and accountability. The book is intended to enrich the theoretical and practical knowledge of scholars who are interested in understanding the leadership of educational institutions, and of principals, marketers, and administrators who face inter-institutional competition in the context of schooling, tertiary or higher education.
The research on school marketing : current issues and future directions : an updated version / Izhar Oplatka, Jane Hemsley-Brown -- Marketisation and education marketing : the evolution of a discipline and a research field / Nick Foskett -- Integrating marketing into the leadership and management of schools : a curriculum-focused approach / Felix Maringe -- Marketing the school "revisited" : the complexity of leadership dilemmas / Tristan Bunnell -- School marketing in the United States : demographic representations and dilemmas for educational leaders / Christopher Lubienski, Matthew Linick, J.G. York -- Public-private collaboration in international education : a New Zealand case study / Christopher Allen Stachowski -- Relationship marketing and school success / Dorit Tubin -- a conceptual framework for classifying and understanding relationship marketing within schools / Hsiao-Pei (Sophie) Yang, Julie Robson -- Forms of market orientation among primary and secondary school teachers in Israel / Izhar Oplatka, Jane Hemsley-Brown -- Educational marketing and the pace of innovation / Miri Yemini -- Creating value in school education marketing through the cocreation process : a conceptual paper / James Seligman -- Reflections on management and leadership of educational marketing : looking toward the future / Jane Hemsley-Brown, Izhar Oplatka.
Includes index.
Keywords: Education -- Administration -- General; Education -- Leadership; Business & Economics -- Education; Organization & management of education; Funding of education & student finance; Education -- Marketing; Educational leadership; School management and organization